New insights on the biological parameters of the exploited cuttlefish Sepia officinalis L. (Mollusca: Cephalopoda) in the northern Adriatic Sea in relation to the main fishing gears employed - BETTOSO, N.; BORME, D.; FARESI, L.; ALEFFI, I.; ORLANDO-BONACA, M.; LIPEJ, L. (Mediterranean Marine Science, 2015)
The cuttlefish (Sepia officinalis Linnaeus 1758) represents one of the most important coastal fishery resources of the Mediterranean Sea. For Italy, 45% of cuttlefish landings (2,328 t) originates from coastal regions of the northern Adriatic Sea: Veneto, Marche, Emilia Romagna and Friuli Venezia Giulia. In terms of economic value this species represents about 8% ( € 16.5 million) of the production from this basin. From May 2004 to October 2005, cuttlefish were purchased from commercial landings of the Grado fishery fleet. At least 30 specimens were randomly taken each month from each fishing method employed for this species: bottom trawl (cod end mesh size 40 mm), rapido trawl, trammel net (mesh size of inner panel 30 mm) and cuttlefish specific trap. The main biological aspects, such as size, sex ratio, reproductive stage and diet in relation to both the season and type of fishing gear were analyzed. 1,495 specimens, ranging from 3.5 to 18.0 cm mantle length, were analyzed. In relation to the observed size and reproductive stage of individuals caught, trammel nets and cuttlefish traps both appeared to target sexually mature individuals, whilst trawling gear were not selective for either recruits or spawners. In total 34 prey taxa were found in the stomachs of S. officinalis: crabs and bony fish species were the most important prey, although the latter appeared mostly in the largest specimens. Finally the fullness index revealed that cuttlefish caught by trawling were more suitable for diet analysis than those caught by static gear. In this way the contribution of the present paper was to give new insights on the biological parameters of this species in relation to the main fishing gears employed in the northern Adriatic Sea.